Suma incisiva superior: estudio en una muestra de la población de Santiago - Catalán C. , Carolina; Jiménez A. , Vila; Guevara G., Fernando; Moreno N., Dantón; Estrada M., Eugenia (Revista Hospital Clínico Universidad de Chile, 1997)
UPPER INCISIVE SUM: STUDY OF A SANTIAGO OF CHILE POPUI.ATION SAMPLE A clinical study of the measurements of the wide of upper and lower incisives is made by a compass and the results obtainedf rom outpatients of the Hospital J.J. Aguirre are compared with that of other authors